Rad American history A-Z : movements & moments that demonstrate the power of the people - Schatz, Kate (Ten Speed Press, 2020)
Presents brief historical information about various events in the United States, organized in an a-to-z format, with each letter of the alphabet introducing one or more events, people, or moments. Includes illustrations and a timeline.